Consequences of Foreign Direct Investment on Inflation - Nhemhafuki, Sanjeev; KC, Subin; Thapa-Parajuli, Resham (Journal of Development and Administrative Studies, 2023)
This paper analyses the relationship between inflation measured in terms of CPI and FDI, GDP, and population. The paper intends to examine the consequences of FDI on inflation. The unbalanced panel data of 88 countries from 1970 to 2021 was employed for the said purpose. The empirical results have been estimated using Pooled OLS, Fixed Effect, and Random Effect Model. Moreover, control variables GDP and Population were introduced to strengthen the causal conclusion. Fixed Effect model was used for the analysis. The pool-ability of the data is tested by the Breusch and Pagan LM test which confirmed that Pooled OLS is not appropriate for the model. The Hausman Specification Test was then conducted to choose between the Fixed Effect or Random Effect model. The Hausman Specification Test for the Model suggests that the fixed effect model is appropriate for data analysis. Thus, fixed effect regression is used to find the consequences of explanatory and the control variables on the dependent variable. FDI as an explanatory variable has a negative relationship with Inflation, even in the case of controlling GDP and Population. The control variable, GDP, displayed a negative association with Inflation, while Population is depicted to have a positive relationship with Inflation.